Enhanced Instantaneous Power Theory with average algorithm for indirect current controlled three-level inverter-based shunt active power filter under dynamic state conditions - Hoon, Yap; Mohd Radzi, Mohd Amran; Hassan, Mohd Khair; Mailah, Nashiren Farzilah (Hindawi Publishing Corporation, 2016)
An enhanced harmonics extraction algorithm based on Instantaneous Power (PQ) Theory is proposed for indirect current controlled (ICC) three-level neutral point diode clamped (NPC) inverter-based shunt active power filter (SAPF). SAPF is famous in current harmonics mitigation for its flexibility in dealing with dynamic state conditions. As for its controller, PQ Theory has served the major role in harmonics extraction algorithm due to its simple implementation features. However, it suffers from serious time delay due to its dependency on sluggish numerical filters. Furthermore, the algorithm is mostly designed to suit the operation of direct current controlled (DCC) SAPF which requires the knowledge of actual SAPF current (injection current). This leads to inaccurate mitigation as the injection current does not possess the exact information on actual source current which suffers from switching ripples problems. Therefore, two major modifications are introduced involving the development of mathematical average algorithm to replace numerical filter for fundamental real power computation and the formation of mathematical current relationship to change DCC to ICC based operation. The proposed algorithm is developed and evaluated in MATLAB/Simulink. From the simulation results, significant improvement in terms of Total Harmonic Distortion (THD) and response time is presented in comparison to conventional algorithm.